Indonesia’s Sustainable Green Economy Policy in the Energy Sector: Challenges and Expectations - Keumala, Dinda; Sabirin, Ahmad; Setiyono, Setiyono; Az, M. Fariduddin; Arranchado, Jimi Rambo (Jurnal Media Hukum, 2000)
This paper comprehensively analyzes the challenges and prospects for achieving a sustainable green economy in Indonesia's energy sector, where fossil fuels dominate approximately 90.4 percent of the domestic energy supply, making the sector a major contributor to emissions. Despite ambitious targets, renewable energy development has progressed slowly, with only 0.97 GW capacity achieved out of a 3.4 GW target by the fourth quarter of 2023. Employing a normative research approach, this study draws from primary and secondary data sources to explore the obstacles hindering green economic transformation, including limited financing for technological innovation, insufficient long-term environmental policies, human resource constraints, institutional structures, regulatory coherence, and the need to balance economic tradeoffs. Key findings highlight that Indonesia must bolster its legal framework, strengthen infrastructure, foster policy alignment, secure financing, enhance technological capabilities, and expand renewable energy capacity. This paper seeks to contribute insights for formulating an integrated, resilient strategy to accelerate Indonesia's transition to a green economy within the energy sector.